Anomalous dislocation core structure in shock compressed bcc high-entropy alloys. (1st May 2021) - Zhao, Long; Zong, Hongxiang; Ding, Xiangdong; Lookman, Turab
Abstract: Recent studies of complex concentrated alloys suggest unusual dislocation core structure and motion, thanks to a collective concentration/structural inhomogeneity. Less is known whether these effects also work in extreme conditions where the solid solution effect is overwhelmed by the large driving force. Here, we investigate the dislocation structure behind a shock-wave front in bcc high-entropy alloys (HEAs) using large-scale molecular dynamics (MD) simulations. In contrast to bcc elemental metals, we find anomalous "extended" edge dislocation structure (6 8 Burgers vector) with high stability in shock compressed TiZrNb and NiCoFeTi HEAs. The unique dislocation structures can facilitate faster dislocation motion, thus deterring the early nucleation of deformation twins. Combined with continuum elasticity theory, we show that the "extended" dislocation structure can be attributed to the presence of local structures with low elastic stability that are imparted by the nanoscale chemical heterogeneities in HEAs. We also show how the dislocation structures are affected by the interatomic potentials. Graphical abstract: Image, graphical abstract